In vitro toxicity of amorphous silica nanoparticles in human colon carcinoma cells. Issue 3 (May 2011) - Gehrke, Helge; Frühmesser, Anne; Pelka, Joanna; Esselen, Melanie; Hecht, Lena L.; Blank, Holger; Schuchmann, Heike P.; Gerthsen, Dagmar; Marquardt, Clarissa; Diabaté, Silvia; Weiss, Carsten; Marko, Doris
Abstract The use of nanostructured silica (SiO2) particles is no longer restricted to biomedical and (bio-) technological fields but rather finding applications in products of the food industry. Thus, our studies on the toxicological relevance of SiO2 nanoparticles focused on cytotoxic effects, the modulation of the cellular redox status and the impact on DNA integrity in human colon carcinoma cells (HT29). The results indicate that these SiO2 nanoparticles stimulate the proliferation of HT29 cells, depending on the incubation time and the particle size. The cytotoxicity of the investigated SiO2 nanoparticles was found to depend on the concentration, size and on the FCS content of the culture medium. Furthermore, SiO2 seem to interfere with glutathione biosynthesis. The results indicate further that effects of SiO2 NPs are not mediated by oxidative stress but by interference with the MAPK/ERK1/2 as well as the Nrf2/ARE signalling pathways. Additionally, investigations regarding DNA integrity revealed no substantial (oxidative) DNA damage.